PENGUATAN KARAKTER SISWA MELALUI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA RAHMATAN LIL’ALAMIN - hermawan, hermawan; firdaus (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This research aims to analyze the strengthening of student character through a project to strengthen the profile of Pancasila students. This implementation was carried out at MAN Purbalingga by creating works in the form of ecoprints as an effort to strengthen character. The implementation of P5RA activities is carried out based on community needs and problems in the educational environment with the aim that students learn from the surrounding environment. With this activity, students dive directly into knowledge, not just theory, but students experience it themselves, as said by Ki Hajar Dewantoro, children must bring their lives closer to the lives of the people so that they not only have knowledge, but can experience it themselves. So the method used is direct practice in making ecoprints. And the results are exhibited in the work title activity.